Analysis of Variances in Flame Length of Time For Maggot BSF Oil with Several Types of Oil - Rimantho, Dino; Hidayah, Nur Yulianti; Pratomo, Vector Anggit; Ramadhan, Anwar Ilmar (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2024)
Three problems are being faced simultaneously by Earth today: water (wastewater), energy, and food. However, considering the finite amount of land and the depletion of fossil fuels, this expansion is incompatible with the replenishment of natural resources in terms of both quantity and quality. Furthermore, another sustainable energy source that has gained international attention is biodiesel. However, research on the relative flash durations of Maggot BSFL oil has not been conducted. Consequently, this article will compare the flame times of many other types of oil with Maggot BSFL oil. This study uses a variety of oils as experimental subjects, including BSF maggot oil, used cooking oil, Pertamina Dex, and a combination of Pertamina Dex and BSF maggot oil. Analysis of the variations in flame time for each type of oil is done using statistical analysis. According to this analysis, the mixture of Maggot BSF oil and Pertamina Dex had the maximum flame, lasting between 16.31 and 16.44 minutes. Additionally, this study offers data on the notable variations in flame length for each type of oil, including used cooking oil, Pertamina Dex, Maggot BSF oil, and a combination of both. When creating biodiesel from Maggot BSF oil, the experiment's findings can serve as a starting point. in order for biodiesel made from Maggot BSF oil to provide Indonesia with a fresh option for the development of sustainable energy.